2020
DOI: 10.1038/s41467-020-19124-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the synthetic biology potential of bacteriophages for engineering non-model bacteria

Abstract: Non-model bacteria like Pseudomonas putida, Lactococcus lactis and other species have unique and versatile metabolisms, offering unique opportunities for Synthetic Biology (SynBio). However, key genome editing and recombineering tools require optimization and large-scale multiplexing to unlock the full SynBio potential of these bacteria. In addition, the limited availability of a set of characterized, species-specific biological parts hampers the construction of reliable genetic circuitry. Mining of currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 176 publications
(213 reference statements)
2
45
0
Order By: Relevance
“…73 reported that the frequency of occurrence of Rif R mutants in a Δ)mutS derivative of P. putida KT2440 was 1,000- fold higher than that in the wild-type strain. Since mutation rates must be precisely controlled to avoid extensive accumulation of deleterious mutations and to prevent genomic instability, the overexpression of mutator alleles should be driven from tightly-regulated expression systems (which is always challenging, irrespective of the bacterial host 74 ) or during short periods of time. Thus, the easy-to-cure mutator plasmids developed in this study, which can be rapidly removed from isolated clones displaying the phenotype of interest, offer a clear advantage over conventional mutator strains—where the mutator phenotype is elicited by genomic (hence, essentially irreversible) modifications, as epitomized by the emergence of mutator phenotypes of P. aeruginosa in clinically-relevant setups 75-77 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…73 reported that the frequency of occurrence of Rif R mutants in a Δ)mutS derivative of P. putida KT2440 was 1,000- fold higher than that in the wild-type strain. Since mutation rates must be precisely controlled to avoid extensive accumulation of deleterious mutations and to prevent genomic instability, the overexpression of mutator alleles should be driven from tightly-regulated expression systems (which is always challenging, irrespective of the bacterial host 74 ) or during short periods of time. Thus, the easy-to-cure mutator plasmids developed in this study, which can be rapidly removed from isolated clones displaying the phenotype of interest, offer a clear advantage over conventional mutator strains—where the mutator phenotype is elicited by genomic (hence, essentially irreversible) modifications, as epitomized by the emergence of mutator phenotypes of P. aeruginosa in clinically-relevant setups 75-77 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their application for the accelerated evolution of phenotypes that depend on multiple mutations across the bacterial genome, the use of these devices also revealed an important feature of the MMR system relevant for synthetic biology. A number of genome modification approaches rely on specifically interfering with the bacterial MMR system to enable strand invasion 51,53,74,83 . Besides the intended modifications (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…While our results provide insight into the limits and capabilities of phage regulatory strategies, our approach may also prove useful for synthetic biology applications in phages [43, 44]. Synthetic genetic circuits are typically designed for free-living species where they must operate in variable cellular contexts over comparatively long time-scales [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage genome engineering offers the possibility of streamlining the process for determining the phage sensitivity of a target bacteria by making the bacterial isolation step redundant [ 16 , 17 ]. In this approach, currently being implemented primarily in the food industry to detect the presence of microbial contamination, engineered bioluminescence-based reporter bacteriophage assays offer the best available method for determining the presence of specific bacteria with a fast turnaround time and without the need for bacterial isolation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%